PRIMARY PALATAL ALK-NEGATIVE ANAPLASTIC LARGE CELL LYMPHOMA: RARITY TREATED SUCCESSFULLY WITH BRENTUXIMAB VEDOTIN - Müjgan Çözeli; Elif Canbolat Hirfanoğlu; Birol Güvenç (Hematology, Transfusion and Cell Therapy)
Introduction: ALCL is an extremely rare T-cell non-Hodgkin lymphoma subtype made up of CD30-positive tumor cells, which are very aggressive. Though it most frequently involves lymph nodes and skin, less frequently, it affects other organs as well. Primary oral involvement, particularly of the palate, is highly uncommon. The paper reports a peculiar case of localized primary ALK-negative ALCL of the palate in a 73-year-old female patient treated successfully with brentuximab vedotin, pointing to the importance of identifying atypical presentations. Case Report: A 73-year-old female with a history of presenting a painless ulcer on her palate, which did not heal with local treatments for two months, presented to the otolaryngology clinic and underwent an incisional biopsy. Histopathological findings showed large atypical lymphoid cells with prominent nucleoli, consistent with ALCL. Immunohistochemical staining was positive for CD30 and negative for ALK; in addition, Epstein-Barr virus testing returned negative.PET-CT showed localized uptake of FDG in the palate, SUVmax 8.5, with no significant lymphadenopathy and no systemic involvement. Bone marrow biopsy showed normal hematopoiesis with no evidence of infiltration. The patient was diagnosed with primary breast ALK-negative ALCL and started on brentuximab vedotin. The patient went into complete remission after three cycles of therapy with no residual disease evident on follow-up imaging. Discussion: This case illustrates the need to consider ALCL in the differential diagnosis of atypical sites, such as the palate, when lesions fail to respond to conventional therapy. Early biopsy and a wide panel of immunohistochemical tests are crucial for accurate diagnosis. Due to the high recurrence rates as well as poor prognosis associated with ALK-negative ALCL, highly active targeted therapies include brentuximab vedotin. The complete remission attained in this patient underlines the promise of personalized therapies in dealing with rare malignancies. Awareness of such atypical presentations may help in early diagnoses and improve patient outcomes. This case further stresses that management of lymphoma with such unusual presentations may be effectively accomplished using an interdisciplinary approach.